Evaluation of Food-Grade Additives on the Viability of Ten Shigella flexneri Phages in Food to Improve Safety in Agricultural Products - Tomat, David Damian (2025)
Bacteriophages can be used as biocontrol agents in agriculture to improve food safety, provided they can remain viable in food environments. The viability of ten Shigella phages (AShi, Shi3, Shi22, Shi30, Shi33, Shi34, Shi40, Shi88, Shi93 and Shi113) was evaluated against different additives and biocides used daily in food applications. In addition, the influence of additives on phage viability in a food matrix was investigated. Treatments with lactic and citric acid were the most effective to inactivate phages. In addition, the acetic acid was the most phage-friendly treatment evaluated. Preservatives such as acetate, lactate, benzoate, sorbate and propionate proved to be highly compatible with all the phages tested. Regarding the influence of the food matrix on phage viability, an equal or higher viability was found for most phages tested when was compared with the corresponding organic acid. Finally, when phages were exposed to sodium hypochlorite, ethanol, quaternary ammonium chloride (QAC) and H2O2, most of them were sensitive to long incubations and high concentrations. However, when biocide concentrations employed are low, 10exp3-10exp4 PFU/ mL phage particles remains viable. Thus, the phages evaluated could be used in combination with additives and biocides as a biocontrol tool against the foodborne pathogen S. flexneri in agricultural products.